Regulação e governança participativa no Brasil: processos, práticas e atores nas agências reguladoras de saneamento básico - Oliva, Gustavo Martins de (2020)
This research analyzes political and institutional elements of the regulation of public basic sanitation services. Evaluates the quality of an essential component of governance – participatory dimension – from two complementary approaches: the implementation level of structures and practices aimed at the participation of stakeholders and the presence of actors in the arenas of participation promoted by the regulatory agencies. To measure the level of participatory governance, a survey was applied with the agencies, based on the composite indicators of a project developed by the OECD - Indicators of Regulatory Policy and Governance (iREG), and to identify the actors present in the arenas for participation, public consultations, hearings and councils existing at the agencies were analyzed. Given the data collected, the research sought to verify the correlation between the level of participatory governance and the presence of actors in the regulatory process, such as those that represent the environmental protection, health promotion, defense of consumers and access by low-income communities to basic sanitation services. It is, therefore, a matter of verifying whether the implementation of participation structures and practices in the agencies promotes the inclusion of these actors and interests in the regulatory process. The research is characterized as a cross-sectional observational study and used comparative and statistical methods. It sought to verify similarities and differences between the Sanitation Regulatory Agencies, using the year 2018 as a period, and making causal inferences through statistical tests.